English Exposure through Social Media and Its Influence on Vocabulary Comprehension: A Case Study of Kampung Inggris Alumni - Ellena, Gaida Viska; Yuntoro Putri, Kristanti; Hari Kurniawan, Erwin; Abdullah Ahmad Albayyan, Ali (Indonesian Journal of Multidisciplinary Educational Research, 2026)
This study aims to explore how English exposure through social media platforms, such as Instagram, TikTok, and YouTube, influences vocabulary comprehension among Kampung Inggris alumni. While social media provides a continuous stream of English input, its impact on adult learners who have completed intensive programs remains under-researched, pointing to a significant research gap. Using a qualitative case study design, data were collected from 15 purposefully selected participants through an open-ended questionnaire. The findings indicate that social media plays a significant role in supporting vocabulary comprehension, primarily through incidental learning processes. Audiovisual content, visual cues, and situational context help learners recognize and infer word meanings without direct translation. Furthermore, learner engagement and content preference were identified as key factors determining the effectiveness of this exposure. Active interaction, such as searching for word meanings, led to better vocabulary retention compared to passive consumption. This research implies that social media serves as a sustainable supplementary learning medium that supports long-term vocabulary development outside the traditional classroom environment.